Changes in serum enzyme levels accompanying cardiac surgery with extracorporeal circulation. Issue 3 (May 1966) - Welbourn, Nora; Melrose, D. G.; Moss, D. W.
Abstract : Serum lactic dehydrogenase, alpha-hydroxy-butyrate dehydrogenase, iso-citric dehydrogenase, and glutamic oxaloacetic transaminase activities were measured daily for two weeks postoperatively in the serum of 22 patients undergoing cardiac surgery with extracorporeal circulation. The length of perfusion was found to be a major factor affecting the extent of increased post-operative enzyme activities. Significantly higher levels were demonstrated in patients perfused for over one hour compared with those perfused for under one hour. Hepatocellular damage, age, and type of operation were not considered to be major factors in determining the extent of this increased activity. A considerable increase in enzyme activity was found to occur during perfusion when the dilution introduced by mixing the patient's circulation with the priming fluid of the heart-lung machine was taken into account. This dilution, when accounted for, increased the observed enzyme activity by 30 to 50%.